Kajian Pustaka: Faktor Penyebab Dasar Pada Terjadinya Kecelakaan Kerja Sektor Konstruksi - Agustian, Ridwan; Ekawati, Ekawati; Wahyuni, Ida (Jurnal Ilmiah Mahasiswa, 2020)
In the last few years, work accidents in the construction sector have increased. Work accidents can hinder and cause harm to the company and related parties. The aim of this paper is to identify variables related to work accidents in the construction sector based on previous studies. The method used in this research was a literature review study. The literatures were conducted online through several websites or internet sites such as Scopus, Sciencedirect, ProQuest, EBSCOhost, Google Scholar, and SINTA. This research was conducted on 20 articles consisting of 6 national articles and 14 international articles. The results of this study indicate that the characteristics of workers which consist of age, education level, and years of service have a significant relationship with work accidents. From all research, articles obtained related to work shift variables, sleep quality, and work fatigue have a significant relationship with work accidents.